THE EFFECT OF SOCIAL MEDIA ATTACHMENT (FACEBOOK) ON SOCIAL MEDIA ADVOCACY AND SOCIAL MEDIA SUPPORTIVE (At Kuala Lumpur Heritage Restaurant) - Dimas Muchtiar; Fanny Achmad; Gugyh Susandy (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2021)
Social media attachment is one of the theories used to examine a person's attachment to the social media they use. In this research, we examine the effect or impact of social media attachment (X) on social media advocacy (Y1) and social media supportive (Y2) (case study of kuala lumpur heritage restaurants). The results of this study indicate that there is an influence between social media attachment to social media advocacy by 58.8% and social media supportive by 59.9%. The impact positively affects the company, no matter how small the influence of social media advocacy and supportive social media will have a good impact on the company. thus customer loyalty can be seen as well as maintained to build better value in the eyes of customers.